Origin and evolution of the Community Health Agent Program in Ceará state - Maria Marlene Marques Ávila (Universidade de Fortaleza, 2011)
Objective: To outline the origin and evolution of the work of Community Health Agents (ACS) in Ceará. Data synthesis: A review of the literature pertaining to the subject and interviews with technicians from Ceará State Health Secretariat (SESA-Ce) and from Ceará Public Health School (ESP-Ce) were the sources of the data collected. Initially, we discussed the social and political scenario in which primary health care developed in the state, emphasizingthe evolution of socioeconomic indicators and infant health. Then, we did a brief exposure of health care model and from then on, we focused on the Community Health Agent Program, since its origin as an emergency program, its integration into the Family Health Strategy, the repercussions of this insertion in the work of the Community Health Agent and the need for training of ACS. Conclusion: A discussion on the process of training of ACS was presented seeking dialogue with the necessary training in face of new health needs of the population, and most of all, strengthening the role of ACS as a mediator between families and health professionals at local level.